-8+6(3u-10)=u

Simple and best practice solution for -8+6(3u-10)=u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8+6(3u-10)=u equation:



-8+6(3u-10)=u
We move all terms to the left:
-8+6(3u-10)-(u)=0
We add all the numbers together, and all the variables
-1u+6(3u-10)-8=0
We multiply parentheses
-1u+18u-60-8=0
We add all the numbers together, and all the variables
17u-68=0
We move all terms containing u to the left, all other terms to the right
17u=68
u=68/17
u=4

See similar equations:

| 15+30=-5(9x-9) | | z=36z^2+2z+106z2+2z+10 | | -1+c=-9+2c | | X/2-x-4/6=5/3. | | 3m=-3(2m+9) | | 2(3x+5)=-28+26 | | 2(6x+3)=3(3x-9 | | 3(-x-3)=4x+9-7x | | 3(-6+2j)=-2(2j-1) | | 1/2x-10=22 | | 2(3x+8)=-28+2 | | r+8.1=-3.9 | | 3+6d=7+6+8d | | 7+4y=-5,y= | | 8x−5=10x−7 | | 6z-3z-1=2z+7 | | 8x-5=10x-78x−5=10x−7 | | 11/5y-3=-2 | | 11-4x-7-6=6 | | 24=33+x | | 12x-15=3(2x+13) | | x+16+x=21 | | -2(8-3h)=2(-6+4h) | | 20x+16=21 | | -5(2+3x)-4x=28 | | |x+2|=|2x+6|+1 | | -8g-1=-9g+9 | | 3(r−6)=9 | | 5(4x+9)=-26+51 | | 2g+2.6=18.6 | | 7.2=0.2m | | 4x+8=−1x−9 |

Equations solver categories